Analisis Maslahah Mudharat dalam Pemanfaatan Konten Promosi pada Program TikTok Affiliate di Media Sosial - Andiana, Della; Ramli, Arif Rahman; Al Mubarak, Muhammad Habibie (Universitas Islam Negeri Alauddin Makassar, 2024)
This study discusses the analysis of maslahah mudharat in the use of promotional content in the TikTok Affiliate program on social media. The TikTok Affiliate program is gaining popularity among users to generate revenue through promotional content. However, in its implementation, there are various challenges such as lack of understanding in data management, ethics in creating promotional content, misuse of other people's videos, and lack of security protection for TikTok Shop users who make content at risk of being misused by irresponsible parties, including fraudsters. The method used is library research with a normative theological approach through literature analysis related to the use of promotional content in the TikTok Affiliate program, as well as academic sources and journals. The data sources used consist of primary data and secondary data. The results of the study show that the use of promotional content in the TikTok Affiliate program can improve content creation skills, creativity, and critical thinking skills in producing effective content. From the perspective of maslahah, the promoted product must meet halal criteria and not contain haram elements. However, in terms of mudharat, there is often a discrepancy between the goods promoted and the goods delivered, which creates the potential for fraud against consumers. This research provides a deeper understanding of how promotional content can be utilized within the framework of maslahah mudharat. Collaboration between users in the creation of effective promotional content can help expand reach and increase audience engagement. In addition, it is important for users to create content that is interesting and relevant to the target market, in order to achieve the desired commission.